A donor hemovigilance study: evaluation of adverse reactions to blood donors at tertiary care teaching hospital - Savaliya, Sheetal M.; Singh, Anil P.; Piparva, Kiran G. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Donor hemovigilance is an important aspect of the hemovigilance system and contributes to decrease the blood donor’s complications and improving blood donor safety and functioning of blood bank. Reporting of adverse reactions associated with blood donations has been covered under National blood donor vigilance programme. This study was carried out to estimate the adverse events in blood donors and to promote their safety. Methods: The study was conducted over a period of 6 months, from 1st January 2017 to 30th June 2017 after getting approval from institutional ethics committee at tertiary care teaching hospital. Prior informed consent was obtained and donor confidentiality was ensured. The donors were observed for adverse event during or after donation. For delayed reactions, donors were requested to contact the researcher or designated departmental staff. Data was collected in case record form. Data entry was done in excel 2013 and appropriate Statistical test (chi square) was applied. Results: During study period total 7970 donors were registered, out of which 53.27% donors have donated their blood in blood camps and 46.72% have in blood bank. Incidence of donor reactions was 1.54%. Incidence of adverse reaction was higher at blood camps (58.53%). Authors found highest number of cases of mild vaso vagal type reactions (53%). Other types of reactions observed were painful arm, hematoma, delayed bleeding, tingling and moderate type of vaso vagal reaction. Conclusions: Authors did not find any major serious events like convulsion, thrombophlebitis or arterial puncture during study period. It considers that safety of donors was maintained.